Fanconi anemia ortholog FANCM regulates meiotic crossover distribution in plants - Li, Xiang (2021)
Meiotic recombination increases genetic diversity and manipulation of its frequency and distribution holds great promise in crop breeding. In Arabidopsis thaliana, FANCM (a homolog of mammalian Fanconi anemia complementation group M) suppresses recombination and its function seems conserved in other species including the rosids Brassica spp. and pea (Pisum sativum), and the monocot rice (Oryza sativa). To examine the role of FANCM during meiotic recombination in lettuce (Lactuca sativa, an asterid), we characterized the function of lettuce LsFANCM and found that it can functionally substitute for AtFANCM in transgenic Arabidopsis plants. Moreover, three independent CRISPR/Cas9-edited lettuce Lsfancm mutants showed reduced pollen viability and seed setting. Unexpectedly, analyses of chromosome behavior revealed that 77.8% of Lsfancm meiocytes exhibited univalents. The normal formation of double-strand breaks in DNA and the discontinuous assembly of synaptonemal complex in Lsfancm mutants supports the hypothesis that LsFANCM might be dispensable for the initiation of meiotic recombination but required for normal synapsis. Furthermore, the frequency of lettuce HEI10 (Human Enhancer of Invasion 10) foci, a marker for Class-I crossovers (COs), was similar between wild-type (WT) and Lsfancm. Strikingly, the distribution of LsHEI10 foci and chiasmata in Lsfancm meiotic chromosomes was markedly different from the WT. A similar alteration in the distribution of Class-I COs was also observed in the Arabidopsis Atfancm mutant. Taken together, these results demonstrate that FANCM is important for shaping the distribution of meiotic Class-I COs in plants, and reveal an evolutionarily divergent role for FANCM in meiotic bivalent formation between Arabidopsis and lettuce.